2007
DOI: 10.1177/1753944707082662
|View full text |Cite
|
Sign up to set email alerts
|

Review: The metabolic syndrome as an endocrine disease: is there an effective pharmacotherapeutic strategy optimally targeting the pathogenesis?

Abstract: The metabolic syndrome (MetS) represents a combination of cardiovascular risk determinants such as obesity, insulin resistance and lipid abnormalities such as hypertriglyceridemia, increased free fatty acids, low high-density-cholesterol and hypertension. As a multiple component condition it imparts a doubling of relative risk for atherosclerotic cardiovascular disease (ASCVD). It is currently controversial which component of the syndrome carries what weight. There is even a considerable debate whether the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 191 publications
(185 reference statements)
0
18
0
2
Order By: Relevance
“…It has been well demonstrated that cardiometabolic risk factors frequently occur in obese youth and that these risk factors tend to cluster: obesity, insulin resistance, hypertension and lipid abnormalities (hypertriglyceridemia, increased free fatty acids, low HDL-cholesterol, increased LDL-cholesterol) are hypothesized to be the underlying mechanisms for this clustering of risk factors, known as the metabolic syndrome (MetS) (Schindler 2007). However, the number of studies examining the impact of physical activity on MetS in youth is limited.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well demonstrated that cardiometabolic risk factors frequently occur in obese youth and that these risk factors tend to cluster: obesity, insulin resistance, hypertension and lipid abnormalities (hypertriglyceridemia, increased free fatty acids, low HDL-cholesterol, increased LDL-cholesterol) are hypothesized to be the underlying mechanisms for this clustering of risk factors, known as the metabolic syndrome (MetS) (Schindler 2007). However, the number of studies examining the impact of physical activity on MetS in youth is limited.…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, the prevalence of MetS is driven by the growing obesity “epidemic”, which is occurring throughout Western society and is particularly notable in south-eastern USA 14. In fact, MetS has reached epidemic proportions across the whole of the USA and, in unison, so has the expression of obesity, glucose intolerance, type 2 diabetes, vascular inflammation and a prothrombotic phenotype 6. It has been reported that the incidence of MetS increases with the severity of obesity and has been observed in 50% of obese adolescents 15.…”
Section: Correlation Of the Increase In Mets Prevalence With Increasimentioning
confidence: 99%
“…Increased concentrations of visceral fat may be also contribute to an IR state, because, by its nature, it is more resistant to the metabolic effects of insulin than subcutaneous fat 6. Instead, it is more responsive to lipolytic hormones, glucocorticoids and catecholamines 53 54.…”
Section: Visceral Obesity and Ffasmentioning
confidence: 99%
See 1 more Smart Citation
“…This activation induces the expression of the fatty acid transport protein and fatty acid translocase, which facilitates the transport of free fatty acids across the cell membrane. Activation of PPARα also directly increases the transcription of enzymes of the peroxisomal β-oxidation pathway and de novo fatty acid synthesis by blocking enzymes such as acetyl-CoA carboxylase and fatty acid synthase (Schindler, 2007). …”
mentioning
confidence: 99%